Comparative analysis of the effectiveness of Textbook-Based Instructions (TBI) vs Material Light Approach (MLA) in Saudi EFL speaking skills classroom - Ali, Imanat; Zuraina, Ali; Ezihaslinda, Ngah (Penerbit UMP, 2025)
This study aims to investigate and compare the effectiveness of Dogme ELT material light approach (MLA) and traditional textbook-based instructions (TBI) in enhancing speaking skills among Saudi English as a Foreign Language (EFL) learners at Majmaah University. Exploring their speaking skills using Dogme ELT material light Instructions is vital to evaluate its impact. In terms of methodology, the study employed a pretest post-test research design to evaluate the effectiveness between intervention and outcome. Pre and post-tests were conducted to see if there was a statistically significant difference in scores among 48 students who were in the experimental and control groups.